English Teachers’ Identity in Pesantren: A Narrative Inquiry Study - Alim, Syahirul; Basthomi, Yazid; Suharyadi, Suharyadi (Jurnal Pendidikan Progresif, 2024)
Abstract: English Teachers’ Identity in Pesantren: A Narrative Inquiry Study. Objective: Pesantren (Islamic Boarding School) is recognized as an educational institution in Indonesia. In educational environment, Teachers have an important role for the successful in the teaching-learning process. They should construct their professionalism and identity in facing the development of education. There are numerous research studies on teacher identity. But, there is still a lack of research on teacher identity in Pesantren. Therefore, this research study aims to explore how English teachers in Pesantrnen construct their identities. Method: This research is a narrative study that involves six English teacher in Pesantren. The data were elaborated into three themes, the novice teacher, the professional learning journey to be professional teachers, and professional teachers. Finding: The examination of their construction identities revealed from the teachers’ experiences to know how teachers in Pesantren understand themselves through experiences. Conclusion: Understanding teachers’ experience will give best implications to the English teachers’ identity which in turn will contribute to construct their identity. Keywords: pesantren, english teachers, teachers’ identity.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202423